Synthesis, photophysical and electroluminescent properties of blue-emitting dual core imidazole–anthracene/pyrene derivatives. Issue 65 (23rd June 2016) - Zhang, Fuli; Li, Weiling; Wei, Donghui; Wei, Xinyu; Li, Zhongyi; Zhang, Shiying; Li, Suzhi; Wei, Bin; Cao, Guangxiu; Zhai, Bin
Abstract : Two blue emitting dual core materials1 and2 consisting of phenanthroimidazole and anthracene or pyrene chromophores were synthesized, and efficient nondoped blue-emitting OLEDs with low onset voltages and little efficiency roll-off were fabricated. Abstract : Two blue emitting dual core materials consisting of phenanthroimidazole and anthracene or pyrene chromophores were designed and synthesized. 2-(9-Anthracenyl)-1-(4- tert -butylphenyl)-1 H -phenanthro[9, 10- d ]imidazole (1 ) and 2-(1-pyrenyl)-1-(4- tert -butylphenyl)-1 H -phenanthro[9, 10- d ]imidazole (2 ) were easily synthesized and used as emitters in nondoped OLEDs. Devices based on1 and2 show low turn-on voltages (as low as 2.6 and 2.5 V) and stable blue emissions with CIE of (0.16, 0.17) and (0.15, 0.12), respectively. The maximum current efficiencies of 1.15 and 0.90 cd A −1 and maximum external quantum efficiencies of 0.83% and 0.85% with little efficiency roll-off at high current densities were achieved, respectively.